A Phylogenomic Study of Acanthamoeba polyphaga Draft Genome Sequences Suggests Genetic Exchanges With Giant Viruses - Chelkha, Nisrine; Levasseur, Anthony; Pontarotti, Pierre; Raoult, Didier; Scola, Bernard La; Colson, Philippe (Frontiers in Microbiology, 2018)
Acanthamoeba are ubiquitous phagocytes predominant in soil and water which can ingest many microbes. Giant viruses of amoebae are listed among the Acanthamoeba-resisting microorganisms. Their sympatric lifestyle within amoebae is suspected to promote lateral nucleotide sequence transfers. Some Acanthamoeba species have shown differences in their susceptibility to giant viruses. Until recently, only the genome of a single Acanthamoeba castellanii Neff was available. We analyzed the draft genome sequences of Acanthamoeba polyphaga through several approaches, including comparative genomics, phylogeny, and sequence networks, with the aim of detecting putative nucleotide sequence exchanges with giant viruses. We identified a putative sequence trafficking between this Acanthamoeba species and giant viruses, with 366 genes best matching with viral genes. Among viruses, Pandoraviruses provided the greatest number of best hits with 117 (32%) for A. polyphaga. Then, genes from mimiviruses, retroviruses, Mollivirus sibericum, marseilleviruses, and Pithovirus sibericum were best hits in 67 (18%), 40 (11%), 35 (9%), 24 (7%), and 2 (0.5%) cases, respectively. Phylogenetic reconstructions showed in a few cases that the most parsimonious evolutionary scenarios were a transfer of gene sequences from giant viruses to A. polyphaga. Nevertheless, in most cases, phylogenies were inconclusive regarding the sense of the sequence flow. The number and nature of putative nucleotide sequence transfers between A. polyphaga, and A. castellanii ATCC 50370 on the one hand, and pandoraviruses, mimiviruses and marseilleviruses on the other hand were analyzed. The results showed a lower number of differences within the same giant viral family compared to between different giant virus families. The evolution of 10 scaffolds that were identified among the 14 Acanthamoeba sp. draft genome sequences and that harbored ≥3 genes best matching with viruses showed a conservation of these scaffolds and their 46 viral genes in A. polyphaga, A. castellanii ATCC 50370 and A. pearcei. In contrast, the number of conserved genes decreased for other Acanthamoeba species, and none of these 46 genes were present in three of them. Overall, this work opens up several potential avenues for future studies on the interactions between Acanthamoeba species and giant viruses.